PENGARUH PRODUK TABUNGAN DAN TANGGUNG RENTENG TERHADAP EFESIENSI MITIGASI RESIKO PINJAMAN DI BAITUT TAMKIN NTB UNIT AIKMEL - Hadratullah; Lilis Indiryawati (Al Birru: Jurnal Keuangan dan Perbankan Syariah, 2022)
Abstract This study aims to examine: The effect of savings products and rent costs partially and significantly on the efficiency of loan risk mitigation in Baitut Tamkin NTB Unit Aikmel, and the influence of savings products and rent costs simultaneously and significantly on the efficiency of loan risk mitigation in Baitut Tamkin NTB Unit Aikmel.This research is quantitative research. The variables in this study are savings products and loan savings and loan risk mitigation efficiencies. The population in this study was 208 people. The sample number was 67. The sampling technique in this study is proportionate random sampling. Data collection techniques use questionnaires, observations and interviews. The analysis technique used is multiple regression.The results showed that: Savings products had a partial and significant effect on loan risk mitigation efficiency shown regression coeffesien value of 0.547 and t calculated value of 3,264 greater than t table 1.999, Rent liability has no partial and insignificant effect with a co-efficiency value of 0.044 and a calculated value of 0.327 smaller than t table 1.999 and simultaneously there is an effect and significant savings and rent responsibility on loan risk mitigation efficiency, indicated by the value F calculated 27.525 greater than F table 3.14. Keywords: Savings Products, Renting Responsibilities, Loan Risk Mitigation